Indonesian Surf Tourism Research: State of the Art - Sarani Pitor Pakan (Program Studi Pariwisata Fakultas Ilmu Budaya Universitas Gadjah Mada Yogyakarta, 2026)
Indonesia is one of the most studied locations in surf tourism literature worldwide. But, for the most part, ‘local’ and ‘insider’ voices have been overlooked, favoring instead surf tourism knowledge produced by those who are ‘outsiders’ to the country. This article responds to such epistemic neglect by putting forward surf tourism research produced by Indonesian scholars residing institutionally in Indonesia-based universities. This corpus of literature, what I call ‘Indonesian surf tourism research’, is however still largely unknown, especially to international audience. Thus, this article aims to provide a state-of-the-art review by consulting with 35 research articles about surf tourism produced in and about Indonesia. The review intends to document what Indonesian surf tourism research looks like, what kinds of knowledge it produces, and what directions it is heading to. This results in the finding and discussion of six key thematic focuses: tourism development, local impacts, surf tourists, tourism package, suitability studies, and tourism promotion. Put together, these themes speak to broader and more international surf tourism literature by adding new case studies and offering distinct, yet sometimes overlapping, perspectives and insights on surf tourism. This article contributes an initial attempt at localizing knowledges about surf tourism in Indonesia, as well as a necessary first step towards more critical Indonesian surf tourism studies.